A STUDY OF POPULAR E-COMMERCE PLATFORMS AND DEMOGRAPHICS PROFILING OF ONLINE CONSUMERS IN INDIA (IITM Journal of Business Studies, 2024)
Past decade has seen a surge in shopping  via online mode by Indian consumers. This  is accompanied by a multifold increase in  e-commerce platforms that are catering to  the diverse needs of these customers. Yet  some e-commerce platforms remains more  popular in the market and others fade out  fast. This study is an attempt to investigate  the popular e-commerce platforms among  Indians in categories namely, food, shopping,  entertainment and transport (cab service).  Further, the study also explores the influence of  demographic variables (gender & age) on the  online shopping behavior of Indian consumers.  Online survey-based questionnaire was used  to collect data from the respondents. Data  analysis and hypotheses testing was performed  using Chi-square test. Analysis revealed that age  differences were important factor influencing  the online shopping behavior of consumers in  India in comparison to gender differences. The findings of the current study will help e-commerce  platforms in strategizing themselves to lure the  untapped age groups in India as more and more   consumers are becoming comfortable with  surfing, ordering and purchasing via the digital  mode.
Keywords: E-comm:erce platforms; Online shopping behavior; demographics; Indian consumers